Wreck-It Ralph - Moore, Rich; Spencer, Clark; Lasseter, John; Johnston, Phil; Reardon, Jim; Lee, Jennifer (Screenwriter); Reilly, John C., 1965-; Silverman, Sarah; McBrayer, Jack, 1973-; Lynch, Jane, 1960-; Tudyk, Alan; Kaling, Mindy; et al. (Burbank, CA : Buena Vista Home Entertainment, 2013)
For decades, Ralph has played the bad guy in his popular video game. In a bold move, he embarks on an action-packed adventure and sets out to prove to everyone that he is a true hero with a big heart. As he explores exciting new worlds, he teams up with some unlikely new friends including feisty misfit Vanellope von Schweetz. Then, when an evil army threatens their world, Ralph realizes he holds the fate of the entire arcade in his massive hands.
Originally released as a motion picture in 2012.
Bonus features: Paperman : theatrical short; Learn how to take your favorite movies on the go: Disney digital copy.
Edited by Tim Mertens ; original score composed by Henry Jackman ; art director, Mike Gabriel.
Voices: John C. Reilly, Sarah Silverman, Jack McBrayer, Jane Lynch, Alan Tudyk, Mindy Kaling, Joe Lo Truglio, Ed O'Neill, Dennis Haysbert.
MPAA rating: PG; for some rude humor and mild action/violence.
DVD, widescreen (2.39:1) presentation; 5.1 Dolby digital (English), 5.1 Dolby digital (French, Spanish), described video.
Keywords: Video game characters -- Drama; Arcades -- Drama; Heroes -- Drama; French language materials; Spanish language materials; Feature films; Comedy films; Animated films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Video recordings for the hearing impaired